Sexual activity in the over 50s population in Ireland - Mc Garrigle, Christine; Kenny, Rose (The Irish Longitudinal Study on Ageing, Trinity College Dublin, 2017)
The majority of adults aged over 50 in Ireland are sexually active, with 59% reporting they had sex in the past 12 months. The majority of sexually active adults were sexually active once or twice a month (36% of sexually active adults) or once or twice a week (33% of sexually active adults). Adults aged 50 and over who consider sex to be an important part of their life are also more likely to be sexually active, with those who consider sex to be very or extremely important being sexually active most frequently. Being sexually active is less likely in older age groups, with 75% of those aged 50 to 64 being sexually active, compared to 23% of those aged 75 and over. In those aged 50 and over, being sexually active is also largely dependent on having a spouse or cohabiting partner. Three quarters (75%) of those married or cohabiting report being sexually active in the past year, compared to 34% of single, separated or divorced respondents, and 13% of widowed respondents. This trend is seen across all age groups. Even so, a small proportion of currently unmarried or un-cohabiting respondents report having a romantic or intimate partner (9%). The large majority of respondents who report a romantic or intimate partner are sexually active (88%). • Sexual activity is related to health; those who consider themselves to be in better health are more likely to be sexually active, as well as those without long term conditions or disabilities, and those with fewer depressive symptoms. Sexual activity is related to quality of life; those who are sexually active report having higher quality of life on average, independent of their age. Sexually active adults tend to be more positive in their perceptions of ageing. They are less likely to consider themselves old and less likely to believe that ageing has negative consequences. Sexual activity is an important part of life for the majority of adults aged 50 and over in Ireland. As such, more research should be conducted to determine the factors which enable and hinder sexual expression in this age group.
PUBLISHED
Keywords: Ageing